Cardiomyopathy related desmocollin-2 prodomain variants affect the intracellular cadherin transport and processing - Pohl, Greta Marie; Göz, Manuel; Gaertner, Anna; Brodehl, Andreas; Cimen, Tolga; Saguner, Ardan M.; Schulze-Bahr, Eric; Walhorn, Volker; Anselmetti, Dario; Milting, Hendrik (Frontiers in Cardiovascular Medicine, 2023)
Arrhythmogenic cardiomyopathy can be caused by genetic variants in cadherins. Since desmosomal cadherins are crucial for cell-cell-adhesion in cardiac desmosomes, their correct localization at the plasma membrane is necessary. Nine desmocollin-2 variants at five positions from various genetic databases (p.D30N, p.V52A/I, p.G77V/D/S, p.V79G, p.I96V/T) and three additional conserved positions (p.C32, p.C57, p.F71) within the prodomain were investigated in vitro using confocal microscopy. Model variants (p.C32A/S, p.V52G/L, p.C57A/S, p.F71Y/A/S, p.V79A/I/L, p.I96L/A) were generated to investigate the impact of specific amino acids. We revealed that all analyzed positions in the prodomain are critical for the intracellular transport. However, the variants p.D30N, p.V52A/I and p.I96V listed in databases do not disturb the transport revealing that some variants may compensate for the loss of the canonical sequence. As disease-related homozygous truncating desmocollin-2 variants lacking the transmembrane domain are not localized in the plasma membrane we predict that some of the investigated prodomain variants may be relevant in the context of arrhythmogenic cardiomyopathy due to disturbed intracellular transport.